Enhancing clean water management skills for public health in Lake Sentani - Andika Prasetya; Calvin R. Rumansara; Bambang Suhartawan; Suyatno Suyatno; Helen Riupassa; Marthina Mini; Hendry Y. Nanlohy (Community Empowerment, 2024)
Lake Sentani has an area of around 9,630 hectares and is situated at an altitude of 72 meters above sea level. Its water is consistently utilized by the residents of Yobeh Village for drinking, cooking, bathing, washing, and toileting. This activity directly impacts the cleanliness and quality of the lake water, consequently affecting public health. Observations have revealed that the community, especially children, suffer from negative impacts such as diarrhea and stomachaches. Hence, the objective of this community service activity is to enhance the understanding and skills of village communities in obtaining clean and hygienic water from Lake Sentani. The methods employed include socialization, training, and mentoring. The outcomes show that the community has developed a new mindset regarding the water potential of Lake Sentani and has acquired excellent skills in managing the lake water to ensure its cleanliness and healthiness.